Rainfall and Discharge Variability in the Senegal River Basin Based on the IHA/RVA - Cheikh Faye (Indonesian Journal of Social and Environmental Issues (IJSEI), 2023)
The hydrological regime of a river is a driving force of its ecosystem. The operation of dams and locks has significant impacts on the hydrological situation of rivers. The objective of this study was to study the change and variability of precipitation and hydrological data in the Senegal River basin and to assess the change in the discharge regime of the Senegal River caused by the operation of the Manantali hydroelectric dam. Based on the IHA (Indicators of Hydrologic Alteration), a range of variability of thirty-three hydrological parameters was calculated and the hydrological alteration associated with the functioning of the dam was quantified. Using the RVA (Range of Variability Approach) method, the hydrological alteration at the Bakel site was evaluated and showed the influence of the dam on the hydrological state. The results showed a strong influence of the dam on the hydrological regime. The fluvial eco-hydrological objectives calculated in this study can constitute certain support for the management of water resources and ecosystems of the Senegal River basin.